Civil Liability of Airport Managers for Consumer Losses from The Perspective of The Compilation of Sharia Economic Law - Rangkuti, Zivana Tiara Amanda; Harahap, Mhd. Yadi (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
Consumers often require effective and convenient air transportation to carry out their daily activities, both for work and personal purposes. Air transportation offers a fast and efficient solution to reach their destination. This research aims to evaluate the consequences of the negligence of Kualanamu Airport officers and managers and to examine how their responsibilities towards consumers based on the perspective of the Compilation of Sharia Economic Law. The method used is normative juridical legal research, which refers to international law and relevant legislation, and uses the Statute Approach (reviewing all regulations relevant to the legal issues discussed) and Conceptual Approach (based on views and doctrines developed in legal science). The results show that many airport facilities have not met functional standards, which causes negligence of officers to still threaten the safety and comfort of consumers. This negligence includes the operationalization of facilities that are not fit for use. In the context of KHES, responsibility includes providing compensation in accordance with the principles of Islamic law governing loss and compensation. Compensation or 'dhaman' aims to overcome the losses suffered by the injured party, both material and immaterial. This is regulated in Book II of the Compilation of Sharia Economic Law article 20 paragraph 37, which states that 'ta'widh' or compensation is reimbursement for real losses paid by the party who committed an unlawful act.